Immunoregulation effects of different γδT cells and toll-like receptor signaling pathways in neonatal necrotizing enterocolitis. Issue 8 (February 2017) - Hui, Lei; Dai, Yi; Guo, Zhi; Zhang, Jiahui; Zheng, Fang; Bian, Xiangli; Wu, Zhimin; Jiang, Qin; Guo, Miaomiao; Ma, Ke; Zhang, Jinping
Abstract : Abstract: The aim of the study was to observe cytokine and T-cell-related toll-like-receptor (TLR) changes in intestinal samples of neonatal necrotizing enterocolitis patients. Four necrotic bowels were collected from neonatal NEC patients with gestational ages of 28 to 29 weeks in our hospital, whereas 4 neonatal patients who underwent intestinal atresia surgery served as the controls. Intestinal flora was examined and IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, IFN-γ, and IL-17 expressions in resected intestine samples, as well as in isolated gamma delta T (γδT) cells, were analyzed immunohistochemically and via quantitative RT-PCR. γδT cells were isolated from the intestinal intraepithelial lymphocytes (IELs) and their TLR4/TLR9 distribution in the intestinal tissues was determined by flow cytometry. The bacterial flora of the neonatal NEC patients' contained significantly higher amounts of Gram-negative Enterobacteriaceae, Klebsiella, and Bacteroides but anaerobic Gram-positive Bifidobacteria occurred significantly less in the NEC than the control group. IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, IFN-γ, and IL-17 expressions in the resected intestine samples and in isolated γδT cells were enhanced in NEC samples compared to the controls. γδT cells were less prevalent in NEC-derived intestinal tissues, but their TLR4/TLR9 expressions were significantly enhanced. The changed bacterial flora in preterm neonatal NEC patients led to an obvious inflammation of the intestines, which was accompanied by reductions of γδT cell localizations to the intestine and a shift of their surface expressions to TLR4 and TLR9.